Asthma - Kerby, Mona. (New York : F. Watts, 1989)
Discusses the different kinds of asthma, their causes, and remedies for asthma attacks.
Includes index.
Bibliography: p. 91-92.
The Science Teacher (N.S.T.A.).
7.0
7.0
7-10.
Keywords: Asthma -- Juvenile literature; Asthma; Asthma